Predictive value of a nomogram model for adverse outcomes in very low birth weight infants with patent ductus arteriosus: A prospective study - Sun, Xuan; Chen, Ling; Gao, Jinzhi (Frontiers in Pediatrics, 2023)
Objective To establish a nomogram model incorporating markers of echocardiography and N-terminal pro brain natriuretic peptide (NT-proBNP) for predicting adverse outcomes of patent ductus arteriosus (PDAao) in very low birth weight infants and to evaluate the predictive values of the model. Methods A prospective study was conducted for very low birth weight infants who were admitted from May 2019 to September 2020. An echocardiogram and blood NT-proBNP test were carried out in the first 48 h after birth, and the arterial duct remained open in all patients. Other data collected included clinical symptoms and infant characteristics. A nomogram model was established to predict the risk of PDAao (including severe BPD, IVH, NEC or death). Internal verifications were performed for the nomogram, and the discrimination and calibration of the model were evaluated by the C-index and calibration curve. Results Eighty-two infants were enrolled and divided into an adverse outcome (AO) group and normal outcome (NO) group with 41 patients in each group. PDA diameter, PDA maximum flow velocity, left atrium diameter/aortic diameter (LA/AO) ratio and NT-proBNP level were independent risk factors for PDAao and were included in the nomogram model. The model presented good discrimination with a C-index of 0.917 (95% CI 0.859–0.975). The calibration curves in showed high consistency and indicated good Correspondence: between the event incidence predicted by the nomogram model and the true incidence of PDAao. Conclusion The nomogram model incorporating the PDA diameter, PDA maximum flow velocity, LA/AO ratio and NT-proBNP level in the first 48 h could early predict the later occurrence of PDAao in very low birth weight infants.